Implementation of Stretching Exercise Intradialytics in Improving Muscle Cramps Symptoms in Patients Undergoing Hemodialysis - Asep Novi Taufiq Firdaus; Ari Yulistianingsih; Rizki Nugraha Agung; Iyar Siswandi (Indonesian Journal of Global Health Research, 2025)
Hemodialysis is the most successful and most frequent therapy used as form therapy replacement kidney therapy hemodialysis own One of the impacts felt by patients is that is cramps muscle cramps is one of the symptom the most common physical problems experienced patient dialysis. This is contraction muscle sudden that is not deliberate and marked with painful great thing happened repeatedly in patients hemodialysis. The purpose of study This analyze influence implementation implementation stretching exercise intradialytic in repair symptom cramps muscles in patients undergoing hemodialysis at Al Ihsan Regional Hospital Bandung. Data collection uses questionnaire, observation and interviews. Research sample as many as 15 patients shared into 2 groups. Research conducted at Al Ihsan Regional Hospital Bandung, room intermittent hemodialysis May -August 2025. results testing use one-way ANOVA test sig. value < 0.05 so that can concluded that there is influence significant before and after given stretching exercise intervention on cramps. Multivariate test on week first and second p value 1,000 or > 0.05 then No There is influence, on week to three 0.106>0.05 no There is influence and on the week to four p values 0.015<0.05 exist influence. Implementation Intradialytic exercise range of motion (ROM) intervention according to SOP shows success in a way practical All participants who received intervention report feeling more comfortable, calm, relaxed, and not too focus to action will therapy hemodialysis.